RANCANG BANGUN APLIKASI REKAM MEDIS BAGI PASIEN UNIT KESEHATAN KAMPUS BERBASIS WEB (Studi Kasus: Universitas Muhammadiyah Ponorogo) - Muhammad Andy Fananca; Aliyadi Aliyadi; Dwiyono Ariyadi (KOMPUTEK, 2020)
To improve health care and processing data for medical records at the Muhammadiyah Ponorogo University campus health unit, a modern medical record information system is needed. The current medical record-recording process in the Muhammadiyah University campus medical unit of Ponorogo is still done by hand, which is by writing in a book and a patient's treatment card. This is running less optimal because an official has to retrieve and retrieve the data that will be needed in a patient's books and treatment cards, so it takes little time and space. The aim of this study is to develop an existing medical record system, becoming a web-based modern medical record system for patients to record clearly and more efficiently. The study begins with observation, study literature, and then follows the design method using the waterfall model, the context diagram design, the flow diagram (DFD), entity relathionship diagram (erd), system interface design and application testing. With the design of this application for medical records, it is hoped to be beneficial and can improve health care at UKK Muhammadiyah University Ponorogo. The design of this medical record application is still in short supply, and few improvements and innovations that the age has developed need to be made.